Large Crown Root Number Improves Topsoil Foraging and Phosphorus Acquisition - Sun, Baoru; Gao, Yingzhi; Lynch, Jonathan P. (Plant physiology (Bethesda), 2018)
Suboptimal phosphorus (P) availability is a primary constraint to plant growth on Earth. We tested the hypothesis that maize (Zea mays) genotypes with large crown root number (CN) will have shallower rooting depth and improved P acquisition from low-P soils. Maize recombinant inbred lines with contrasting CN were evaluated under suboptimal P availability in greenhouse mesocosms and the field. Under P stress in mesocosms, the large-CN phenotype had 48% greater root respiration, 24% shallower rooting depth, 32% greater root length density in the topsoil, 37% greater leaf P concentration, 48% greater leaf photosynthesis, 33% greater stomatal conductance, and 44% greater shoot biomass than the small-CN phenotype. Under P stress in the field, the large-CN phenotype had 32% shallower rooting depth, 51% greater root length density in the topsoil, 44% greater leaf P concentration, 18% greater leaf photosynthesis, 21% greater stomatal conductance, 23% greater shoot biomass at anthesis, and 28% greater yield than the small-CN phenotype. These results support the hypothesis that large CN improves plant P acquisition from low-P soils by reducing rooting depth and increasing topsoil foraging. The large-CN phenotype merits consideration as a selection target to improve P capture in maize and possibly other cereal crops.